Analysis of Non-Formulary Prescription Compliance in BPJS Patients at Harapan Kita Children’s and Mother’s Hospital, Jakarta - Dola Veronica Agustia; Agusdini Banun Saptaningsih; Natsir Nugroho (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Non-formulary drug utilization in Harapan Kita Children’s and Mother’s Hospital presents a substantial challenge in healthcare cost management, especially for patients enrolled in the BPJS health insurance program. Given its status as a national referral hospital, Harapan Kita Children’s and Mother’s Hospital encounters a high prevalence of complex maternal and child health cases requiring the use of medications beyond the scope of the national formulary. This research endeavor seeks to examine the patterns and consequences of non-formulary drug use within this context. This study adopted a quasi-experimental design, incorporating both quantitative and qualitative methods, to evaluate the impact of an sosialisation intervention and audit clinic on physician compliance with formulary drug use. A pre-test and post-test design was employed to measure changes in non-formulary drug utilization. Findings indicated a statistically significant decrease in non-formulary drug use from 18% to 13% post-intervention. The integration of a clinical pathway and tailored physician training was instrumental in achieving improved formulary adherence. Given these results, it is recommended to broaden training and surveillance programs, strengthen technological support through the implementation of formulary information systems, and undertake longitudinal research to assess the long-term sustainability of the intervention's effects..